Unlocking Managerial Performance: The Impact of Organizational Culture and Employee Personality through Knowledge Sharing: Membuka Kinerja Manajerial: Dampak Budaya Organisasi dan Kepribadian Karyawan melalui Berbagi Pengetahuan - Arizki, Muta’aal Afrian; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2023)
In the modern corporate landscape, the optimization of human resources stands as a pivotal concern for organizations. This study endeavors to explore the influence of organizational culture and employee personality on managerial performance, with knowledge sharing as a mediating variable. Employing rigorous empirical methods, our findings reveal that both organizational culture and employee personality exert both direct and indirect effects on managerial performance, mediated by knowledge sharing. This research underscores the significance of fostering a conducive organizational culture and understanding employee personalities to enhance overall managerial performance. These insights hold substantial implications for businesses striving to maximize their human resource potential in today's competitive environment. Highlights: Organizational Culture: Investigates the influence of organizational culture on managerial performance, emphasizing the importance of a conducive workplace environment. Employee Personality: Explores how employee personality traits impact managerial performance, shedding light on the role of individual differences. Knowledge Sharing: Highlights the mediating role of knowledge sharing in the relationship between organizational culture, employee personality, and managerial performance, emphasizing its significance for effective human resource management. Keywords: Organizational Culture, Employee Personality, Managerial Performance, Knowledge Sharing, Human Resource Optimization